SOCIAL SCIENCE PERSPECTIVES ON AUDIENCE BEHAVIOR IN PERFORMING ARTS - Damodaran B; Gayathri M; Sathya Arthi R; Leka H; Anandhi D; Arumugam, Mahendran (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Information on how the audience perceives, interpret and interact with the performance is vital in the case of artists, cultural institutions and policy makers. The paper will elaborate on the audience behavior in performing arts under the multi-disciplinary social science approach by incorporating the knowledge of sociology, psychology, and study of communication. Their paper reviews literature conducted regarding the aspect of audience research and explores the presence of theoretical frameworks that can be used to elucidate the aspects of cultural participation, perception and reception of performance by an audience. These elements as demographic features, cultural identity, emotional and cognitive involvement, social interaction and technological advances are regarded as the significant elements of the audience behaviour. The paper also examines how the audience engages and participates in different performance environments like in live theatre, dance and music performance and in digital or virtual performance platform. The audience analysis makes the differences in the audience response in both traditional and modern-day performance environment, the audience in a situation of various cultures. The paper further elaborates how the study of audience behavior contributes to the management of performing arts, the formulation of policies in culture management, marketing policies, and analysis basing on the data of the audience. The findings show that association between the social backdrop, psychological experience and the evolving technological settings are complex to affect the audience engagement. Live shows are personal communal and immersive with digital platforms and new technologies expanding the awareness of the audience and their participation. The study concludes by outlining the key challenges of the audience research including a constraint on the data collection process, the question of ethics of audience analytics, and the required interdisciplinary of the future research. The analysis will assist in comprehending the audience behaviors more appropriately as it will introduce the knowledge of social science to the process and apply it to the contemporary approaches toward the practice of performance to develop more inclusive and sustainable performing arts systems.